2018
DOI: 10.1016/j.ijrobp.2017.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Reirradiation or Systemic Therapy in Patients With Glioblastoma After Tumor Progression: A Secondary Analysis of NRG Oncology/Radiation Therapy Oncology Group Trial 0525

Abstract: Patients who received no salvage treatment had poorer survival than those who received radiation, chemotherapy, or the combination. However, patient selection for no treatment likely reflects poorer expected prognosis. There was no significant survival difference among those receiving radiation therapy, systemic therapy, or both. Ongoing clinical trials will help define the role of reirradiation after glioblastoma progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…There are only very few prospective reports on the efficacy of re-RT. Shi and colleagues recently published the late results from RTOG 0525 trial [37]. Patients received BSC only had an mOS of 4.8 months versus the groups treated with re-RT only, chemotherapy only or radiochemotherapy, 8.2, 10.5, 11.3 months, respectively [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only very few prospective reports on the efficacy of re-RT. Shi and colleagues recently published the late results from RTOG 0525 trial [37]. Patients received BSC only had an mOS of 4.8 months versus the groups treated with re-RT only, chemotherapy only or radiochemotherapy, 8.2, 10.5, 11.3 months, respectively [37].…”
Section: Discussionmentioning
confidence: 99%
“…Shi and colleagues recently published the late results from RTOG 0525 trial [37]. Patients received BSC only had an mOS of 4.8 months versus the groups treated with re-RT only, chemotherapy only or radiochemotherapy, 8.2, 10.5, 11.3 months, respectively [37]. It should be noted that in this study OS was calculated from the first progression and not from the beginning of re-RT, as it is in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Role of re-RT for progressed GBL can be reflected in an analysis of patients enrolled in the RTOG 0525 trial. After progression, the median overall survival (OS) after re-RT was better compared to supportive care only (8.2–12.2 months vs. 4.8 months) [6].…”
Section: Re-rt Alonementioning
confidence: 99%
“…The radionecrosis chance was <5% [27]. Another study has found an improvement of median OS by combining re-RT with unspecified chemotherapeutic agents (12.2 vs. 8.2 month) [6].…”
Section: Re-rt With Combined Chemotherapymentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most prevalent and aggressive form of primary brain tumors in adults, the current standard of care for which includes surgical recession of tumor followed by radio-and chemotherapies [1][2][3]. However, the extensive infiltrative nature of GBM tumors makes complete surgical recession difficult.…”
Section: Introductionmentioning
confidence: 99%